Thermodynamic Evaluation of the Hybrid Combined Cycle Power Plant in the Valley of Mexico - Ladislao Eduardo Méndez-Cruz; Martín Salazar-Pereyra; Raúl Lugo-Leyte; Mauricio Sales-Cruz; Alejandro Torres-Aldaco; Helen D. Lugo-Méndez (Energies)
Modern power generation aims to maximize the extraction of thermal energy from fossil fuels to produce electricity. Combined cycle power plants, leaders in efficiency, sometimes require an additional steam generator to compensate for insufficient exhaust gas energy in the heat recovery steam generator (HRSG), leading to hybrid combined cycles. This study presents a comprehensive thermodynamic analysis of the hybrid combined cycle power plant located in the Valley of Mexico, operating under both full-load and partial-load conditions. The investigation begins with an energy analysis evaluating key performance parameters under real operating conditions, including the power generation, heat flow supply, thermal efficiency, fuel consumption rates, steam flow, and specific fuel consumption. Subsequently, the analysis examines the performance of the steam cycle using the β factor, which quantifies the relationship between heat flows in the steam generator and the HRSG, to maintain a constant steam flow. This evaluation aims to determine the potential utilization of exhaust gas residual energy for partial steam flow generation in the steam turbine. The study concludes with an exergy analysis to quantify the internal irreversibility flows within the system components and determine the overall exergy efficiency of the power plant. The results demonstrate that, under 100% load conditions, the enhanced utilization of exhaust gases from the HRSG leads to fuel savings of 33,903.36 tons annually and increases the exergy efficiency of the hybrid combined cycle power plant to 54.08%.